Analisa Pengaruh Penggunaan Serat Serabut Kelapa dalam Presentase Tertentu pada Beton Mutu Tinggi - Eduardi Prahara; Gouw Tjie Liong; Rachmansyah Rachmansyah (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The use of additional material as ingredients in the manufacture of concrete mixes is increasingly growing. The material used is also increasingly varied, depending on the expected results. This research aims to know the influence of the addition of coconut fibres material with percentage of 1,5 %, 2 %, 2,5 %, and 3 % as an alternative to the strength of high-quality concrete. Research methods done by producing cylindrical and beam concrete samples for testing against the force then conducted concrete. Furthermore, the analysis has been done and the results of testing and comparing the respective strength of the composition of concrete produced. Based on the test results of data concrete cylinder compression strength and tensile strength concrete beams, it was concluded that the increasing of compressive strength up to 9% can be reached by use of additional material coconut fibers 1,5%and increasing of tensile strength up to 19,7% can be reached by use of additional coconut fiber 2%. Therefore, the additional coconut fibers on concrete mixture has strong relationship to increase tensile strength of high strength concrete.